Social structures and democracy in the 1990s - Marshall Wolfe (CEPAL Review, 1990)
This article gives a broad overview of the social structures on which democracy will have to be based in the 1990s. These structures continue to be heterogeneous, and the crisis has made them more unstable, as previous aspirations are falling by the wayside and most of the groups are living in conditions of greater insecurity and poverty, although some new possibilities of upward mobility are emerging, even among the most seriously marginated strata. The political parties and movements are in a process of evolution and are unsure of the forces they will be called on to represent and the validity of their traditional ideologies; for the most part, however, they have attained a higher level of realism and a willingness co temporize with a view to the consolidation of broad social pacts at the cost of a reduction in their aspirations and an inability to offer their followers an inspiring mythology.